In Vivo Cosmetic Product Efficacy Testing by Analyzing Epidermal Proteins Extracted from Tape Strips - Marie Westman; Tamara Al-Bader; Eve Merinville; Kevin Cattley; Virginie Lafon-Kolb; Josephine Darbon; Alain Mavon; Aurelie Laloeuf (Cosmetics, 2014)
The objective of this in vivo pilot study was to investigate whether differential biomarker analysis from skin tape strips could be used, not only to evaluate the difference between treated and untreated skin, but also to evaluate the effect of different product treatments. Ten volunteers were included in the study, applying two different basic formulations on their forearms. After four weeks of product application, and also after one week of treatment remission, tape strips were collected from the different treatment sites, as well as from untreated skin. The biomarkers investigated were selected to cover different aspects of epidermal differentiation and in connection with moisturization and barrier function. Levels of Involucrin were increased in both treatments, compared to untreated skin, whereas the levels of Keratin-6 were decreased for both treatments. In addition, a pattern for increased levels of Hornerin and Claudin-1 was also detected. There were no significant differences between the two treatments, only for treatment compared to untreated, but there were tendencies for different effect on some of the biomarkers investigated, differences that may reach significance with increased sample size. The major differences between the two treatments in this study were seen after one week of product remission, although due to too small sample size these differences were not significant.